Analisis kepuasan konsumen ditinjau dari harga, kualitas produk dan lokasi di kedai damoni kopi kediri 2021 - Chrisando, David; Sumantri, Bambang Agus; Ratnanto, Sigit (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2021)
Nowadays the increase in the coffe shop bussines is growing, this is due to the coffe culture in the community which is also developingwhich is becoming a connoisseur of manualy brewed coffe, especially among young people. The purpose of this study was to analyze the significant effect of price, product quality, and location on consumer satisfaction at Kedai Damoni Kopi kediri partially and simultaneously. The approach in this study uses quantitative methods using a sample of 40 respondens and analyze using multiple linier regression analysis. The result of the study obtained the equation Y= -1.354 + 0,237X1+0,384X2+0,291X3. The conclusion of this study is that price, product quality and location partially have a significant positive effect and jointly have a significant effect on consumer satisfaction with a significant value of 0,00<0,05